2005
DOI: 10.1631/jzus.2005.b0396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium composition on the production of plasmid DNA vector potentially for human gene therapy

Abstract: Plasmid vector is increasingly applied to gene therapy or gene vaccine. The production of plasmid pCMV-AP3 for cancer gene therapy was conducted in a modified MBL medium using a recombinant E. coli BL21 system. The effects of different MMBL components on plasmid yield, cell mass and specific plasmid DNA productivity were evaluated on shake-flask scale. The results showed that glucose was the optimal carbon source. High plasmid yield (58.3 mg/L) was obtained when 5.0 g/L glucose was added to MMBL. Glycerol coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In addition, other authors suggest that the plasmid yields obtained from culture were highest into stationary phase. High specific growth rates are associated with acetate production, plasmid instability and lower percentages of supercoiled plasmid overall (Xu et al, 2005). The FDA recognizes that open-circle, linear and nicked forms may be fewer effectives therapeutically than supercoiled DNA.…”
Section: Fermentation Process To Produce Plasmid Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, other authors suggest that the plasmid yields obtained from culture were highest into stationary phase. High specific growth rates are associated with acetate production, plasmid instability and lower percentages of supercoiled plasmid overall (Xu et al, 2005). The FDA recognizes that open-circle, linear and nicked forms may be fewer effectives therapeutically than supercoiled DNA.…”
Section: Fermentation Process To Produce Plasmid Dnamentioning
confidence: 99%
“…It was reported that the media composition affected cell specific growth rate, and thus influenced in plasmid copy number. Therefore, the effects of medium components on cell growth and plasmid productivity should be evaluated (Xu et al, 2005). Media composition can dramatically affect yield and consequently the overall cost of production.…”
Section: Culture Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, the effects of the components in a medium on cell growth and plasmid production should be evaluated to solve the trade-off between higher copy number and reduced growth rate. Acetate accumulation is also a major concern for medium design and high density fermentation of recombinant E.coli because it inhibits cell growth and protein expression (Xu et al 2005). Nevertheless, sometimes acetate addition improves pDNA yield in the experimental system.…”
Section: Overview Of Production Flowsheet Strategiesmentioning
confidence: 99%
“…Nevertheless, sometimes acetate addition improves pDNA yield in the experimental system. This suggests that low rates lead to high specific pDNA yield provided the cell growth is not seriously inhibited by acetate (Xu et al 2005). The use of reduced growth rate is the unifying principle in high quality, high yield plasmid fermentations.…”
Section: Overview Of Production Flowsheet Strategiesmentioning
confidence: 99%